Tal Brasil, qual América? a América Brasileira e a cultura ibero-americana - Piazza, Maria de Fátima Fontes (Diálogos Latinoamericanos, 2007)
This article shows how the magazine – “América Brasileira: Resenha da Actividade Nacional” (1922-1924) -, published by the writer Elysio de Carvalho (1880-1925), wanted to shed light on the Iberian-American literature and the relevant cultural questions of the two sides of America: the Lusitanian and the Hispanic. The magazine is dedicated to some of the personalities of the Iberian world, from Hispanic America: Rubén Darío and Rufino Blanco- Fombona; from Spain: Juan Valera, Ramón Gómez de la Serna and Azorín; from Brazil: Graça Aranha and Ronald de Carvalho. The analysis of the magazine shows how his editorial treated the coexistence between nationalism and cosmopolitanism, between tradition and modernity, so to avoid efforts to reduce the impact of the peripheral position of the Brazilian society regarding cultural welfare.